Bioactive glass air‐abrasion promotes healing around contaminated implant surfaces surrounded by circumferential bone defects: An experimental study in the rat - Abushahba Faleh; Areid Nagat; Gürsoy Mervi; Willberg Jaana; Laine Varpu; Yatkin Emrah; Hupa Leena; Närhi Timo O (Wiley, 2026)
Objectives: The present study aimed to evaluate the healing of experimentally induced bone defects around contaminated dental implants after air-abrasion using 45S5 or zinc oxide (ZnO)-containing bioactive glasses (BAGs).
Materials and methods: One maxillary first molar was extracted from each Sprague-Dawley rat (n = 30). After 4-week healing, a titanium implant was placed in the extraction site with a circumferential bone defect. The rats were randomized into five different groups: (1) implants with Fusobacterium nucleatum and Porphyromonas gingivalis dual-species biofilm (IB); (2) implants with biofilm subjected to inert glass air-abrasion (inert); (3) sterile implants (S); (4) implants with biofilm subjected to 45S5 BAG air-abrasion (45S5); and (5) implants with biofilm subjected to ZnO-containing BAG air-abrasion (Zn4). After 8-week healing, maxillae were dissected, and histomorphometric analyses were performed.
Results: The first bone-to-implant contact was significantly shorter for the inert (1.58 ± 1.16 mm; p = 0.016), S (0.28 ± 0.13 mm; p < 0.001), 45S5 (0.41 ± 0.28 mm; p < 0.001), and Zn4 (0.26 ± 0.16 mm; p < 0.001) groups compared to IB group. Also, significantly more bone-to-implant contact was seen for S (72.35% ± 8.32%; p < 0.001), 45S5 (57.91% ± 24.10%; p = 0.002), and Zn4 (70.49% ± 12.74%; p < 0.001) groups than the IB group. The bone volume with the threads demonstrated significantly higher value for S (69.32% ± 9.15%; p < 0.001), 45S5 (58.93% ± 23.53%; p = 0.001), and Zn4 (68.65% ± 12.41%; p < 0.001) groups compared to the IB group. The bone volume within the defects was significantly higher for S (68.79% ± 11.77%; p < 0.001), 45S5 (62.51% ± 20.51%; p = 0.002), and Zn4 (73.81% ± 15.07%; p < 0.001) groups compared to the IB group.
Conclusions: This study suggests that air-abrasion of contaminated moderately rough implant surfaces with either 45S5 or ZnO-containing BAGs enhances osseointegration and bone defect regeneration.